Advancing the Human Self Do Technologies Make Us "Posthuman"? - Nowak, Ewa (DIA-LOGOS, 2020)
Do technologies advance our self-identities, as they do our bodies, cognitive skills, and the next developmental stage called postpersonal? Did we already manage to be fully human, before becoming posthuman? Are we doomed to disintegration and episodic selfhood? This book examines the impact of radical technopoiesis on our selves from a multidisciplinary perspective, including the health humanities, phenomenology, the life sciences and humanoid AI (artificial intelligence) ethics. Surprisingly, our body representations show more plasticity than scholarly concepts and sociocultural narratives. Our embodied selves can withstand transplants, bionic prostheses and radical somatechnics, but to remain autonomous and authentic, our agential potentials must be strengthened - and this is not through 'psychosurgery' and the brain-computer interface.